REKONSTRUKSI FUNGSI PERS DALAM UNDANG-UNDANG NOMOR 40 TAHUN 1999 TERHADAP PENEGAKAN HUKUM TINDAK PIDANA KORUPSI DI INDONESIA BERBASIS NILAI KEADILAN - Agus Wibowo (Jurnal Pembaharuan Hukum, 2015)
Corruption increasingly widespread, more systematic and more sophisticated. Corruption in this country is like a vicious circle that is difficult to eradicate. The corrupt one with the other criminalswho help each other, work together and protect each other. Corruption as a phenomenon like “snowball”, if the crimes of corruption committed by one or a group of people uncovered, then another group would come out anyway. Therefore, corruption is an extraordinary crime that eradication also requires extra effort. The role of mass media in the political framework of this criminal according to Hoefnagels aligned with political efforts criminals who else is Criminal Law Application (Practical Criminology), namely prevention crime by means of criminal law and Prevention Without Punishment namely the prevention of offenses through means outside the criminal law.